Komposit Nano Struktur Keramik Logam untuk Peningkatan Efisiensi Energi pada Sistem Dirgantara dan Pertahanan - Fazly Arif; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
This study comprehensively reviews the development and application of metal nano-ceramic composites as high-performance materials for improving energy efficiency in aerospace and defense systems. A literature review was conducted on various reputable international scientific publications such as the Journal of the American Ceramic Society, Composites Part A: Applied Science and Manufacturing, Advanced Engineering Materials, and International Materials Reviews. The analysis results show that SiC, ZrC, HfC, and Al₂O₃-based materials have thermal resistance above 2000 °C, high thermal conductivity, and mechanical strength up to 60% greater than conventional materials. Physically, the increase in energy efficiency is explained by Fourier's law q=−k*dT/dx which describes the heat transfer rate and the micromechanical model σc=Vfσf+(1−Vf)σm which describes the interphase strength distribution of the composite. Microstructural engineering and additive manufacturing technologies play an important role in optimizing the strength-to-weight ratio, thermal stability, and aerothermal resistance in high-speed defense systems. Thus, the development of ceramic-metal nano-structure composites has great potential to support energy efficiency and independence of national defense technology.